Strategi Manajemen untuk Kepemimpinan Visioner: Menyatukan Visi Melalui Prinsip-Prinsip Manajemen - Sa’idy, Sa’idy; Sunarto, Sunarto; Asyha, Agus Faisal (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2023)
The low quality which will automatically produce quality education is believed to be the cause of the low quality of human resources. The demand for increasing educational productivity lies not only in improving and increasing the quality of input and output, but also in the quality of the process which is driven by the managerial strength and leadership of education managers both at the central level (education bureaucrat level), at the institutional level (Principal). Based on the description of the background of the problem above, the author can formulate the problem as follows: How is the visionary leadership on the Spirit of Integrity indicator at MAN I Bandar Lampung and MAN I Metro. How is visionary leadership in the Agent of Change indicator at MAN I Bandar Lampung and MAN I Metro. This research was carried out using a qualitative descriptive approach. By using the exspos facto method, namely searching for facts on natural objects with the right interpretation. Research location MAN I Bandar Lampung and MAN I Metro. Research data was collected through observation, interviews and documentation. Based on the data analysis, the following findings and conclusions were obtained: First, MAN 1 Bandar Lampung shows more prominent collective leadership, principals, deputy principals and educational consultants, united in moving the school organization. Visionary leadership at MAN I Metro is seen as more prominent individual leadership, because the principal often carries out work without needing his subordinates. Meanwhile, MAN 1 Bandar Lampung is seen to be more prominent in its democratic leadership